Formação centrada na escola em comunidade de prática cultivada nos anos finais do ensino fundamental - (:unkn) unknown (Universidade Federal do Pampa, 2025)
This thesis investigates how a community of practice can contribute to School-Centered Training for multi-area teachers in the final years of Elementary School. [...] The study was conducted in a qualitative approach, with exploratory and descriptive objectives. [...] The main theoretical references are Pedro Ribeiro Mucharreira, Antonio Nóvoa, Francisco Imbernón, Jean Lave, Ettiene Wenger and Márcia Cristina Cyrino. [...] Issues inherent to the professional profile, teaching know-how and main training demands were investigated. [...] Training actions were organized to meet the immediate demand of the selected school's teachers. [...] Changes were observed in teachers' attitudes regarding participation in pedagogical meetings [...]. Bureaucratic demands promoted by the maintainer were shown to cause discomfort and overload. [...] Finally, the thesis advocates for a School-Centered Education [...] highlighting the importance of developing formative actions with teachers, not just for teachers. [...] The evidence demonstrates the potential of CoPs in promoting a sense of belonging among teachers and improving pedagogical practice. One of the main challenges for CoP development is teaching overload and demands disconnected from reality. [...] The thesis aims to serve as a support for researchers to explore interventions that contribute to School-Centered Training.
School-centered training in a community of practice cultivated in the final years of elementary school
Keywords: Context; Teaching practice; School; Teacher training; Contexto; Prática docente; Escola; Formação de professores; CNPQ::CIENCIAS HUMANAS